Structural properties of target binding by profilaggrin A and B domains and other S100 fused-type calcium-binding proteins. Issue 1 (October 2020) - Hinbest, Alexander J.; Kim, Sa Rang; Eldirany, Sherif A.; Lomakin, Ivan B.; Watson, Joseph; Ho, Minh; Bunick, Christopher G.
Highlights: S100 fused-type proteins have distinct surface chemistries at target binding site Inter-EF-hand linker residues help S100 fused-type proteins anchor substrate Profilaggrin B domain works with A domain to bind and stabilize protein targets Profilaggrin AB complex binds coiled-coil region of keratin intermediate filaments Annexin 2 domains I and II are positioned to interact with profilaggrin B domain Abstract: Background: Profilaggrin belongs to the S100 fused-type protein family expressed in keratinocytes and is important for skin barrier integrity. Its N-terminus contains an S100 ("A") domain and a unique "B" domain with a nuclear localization sequence. Objective: To determine whether profilaggrin B domain cooperates with the S100 domain to bind macromolecules. To characterize the biochemical and structural properties of the profilaggrin N-terminal "AB" domain and compare it to other S100 fused-type proteins. Methods: We used biochemical (protease protection, light scattering, fluorescence spectroscopy, pull-down assays) and computational techniques (sequence analysis, molecular modeling with crystallographic structures) to examine human profilaggrin and S100 fused-type proteins. Results: Comparing profilaggrin S100 crystal structure with models of the other S100 fused-type proteins demonstrated each has a unique chemical composition of solvent accessible surface around the hydrophobic binding pocket. S100 fused-type proteins exhibit higher pocket hydrophobicity than soluble S100 proteins. The inter-EF-hand linker in S100 fused-type proteins contains conserved hydrophobic residues involved in binding substrates. Profilaggrin B domain cooperates with the S100 domain to bind annexin II and keratin intermediate filaments in a calcium-dependent manner using exposed cationic surface. Using molecular modeling we demonstrate profilaggrin B domain likely interacts with annexin II domains I and II. Steric clash analysis shows annexin II N-terminal peptide is favored to bind profilaggrin among S100 fused-type proteins. Conclusion: The N-terminal S100 and B domains of profilaggrin cooperate to bind substrate molecules in granular layer keratinocytes to provide epidermal barrier functions.